The description of prosocial behavior in terms of gender among middle school students in Padang City - Rozi Sastra Purna; Fitri Angraini (Jurnal Psikologi Tabularasa, 2024)
Abstract: The purpose of this study was to determine the description of the prosocial behavior of junior high school students in Padang City. This study uses a quantitative approach with a survey method. The research instrument used a questionnaire in the form of a scale based on indicators of prosocial behavior. The participants were 400 junior high school students in Padang City, consisting of 164 male students and 236 female students. The results showed that there were 205 students in the high category, meaning that students were able to display and demonstrate prosocial behavior; and as many as 195 students in the low category, meaning that students have not been able to display and show prosocial behavior. Furthermore, there is a significant difference between the prosocial behavior of male and female students.Keywords: Students, Junior High School, Prosocial Behavior Abstrak: Tujuan penelitian ini adalah mengetahui gambaran perilaku prososial siswa Sekolah Menengah Pertama di Kota Padang. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survey. Instrumen penelitian menggunakan kuesioner berbentuk skala berdasarkan indikator perilaku prososial. Partisipan penelitian adalah siswa Sekolah Menengah Pertama di Kota Padang yang berjumlah 400 orang, terdiri dari 164 siswa laki-laki dan 236 siswa perempuan. Hasil penelitian menunjukkan terdapat 205 siswa dalam kategori tinggi, artinya siswa mampu menampilkan dan menunjukkan perilaku prososial; dan sebanyak 195 siswa pada kategori rendah, artinya siswa belum mampu menampilkan dan menunjukkan perilaku prososial. Selanjutnya terdapat perbedaan yang signifikan antara perilaku prososial siswa laki-laki dan perempuan. Kata kunci : Siswa, Sekolah Menengah Pertama, Perilaku Prososial